Plate-Controlled Correction of Sagittal Plane Knee Deformities: The Entire-Segment Rotation Technique for Correcting Varus and Posterior Tibial Slope - Akram Aldawoudy, M.Ch.(Orth), F.R.C.S., IOC Dip. Sports Phys., M.Sc. S.E.M.; Mohamed Abohatab; Mohamed Ayman Aboutawila, B.P.T.; Mahmoud Elagwany, M.Ch.(Orth).; Hesham Mohamed Gawish, M.D. (Arthroscopy Techniques)
Sagittal-plane deformity around the knee is usually overlooked. Correction of the sagittal plane may be performed alone or simultaneously with coronal plane correction. This proposed technique ensures an effective rotational control of the proximal tibial fragment along with precise intraoperative correction of the posterior tibial slope in degrees instead of millimeters, exactly as it was preplanned in degrees.